PROBLEM BASED LEARNING DALAM PEMBELAJARAN IPAS: EVALUASI KOMPREHENSIF AKTIVITAS DAN HASIL BELAJAR SISWA KELAS IV SD - Dwi Auliyani; Abidinsyah Abidinsyah (Inteligensi : Jurnal Ilmu Pendidikan, 2026)
This study aimed to improve students' learning activities and learning outcomes in Science and Social Studies (IPAS) through the implementation of the Problem Based Learning (PBL) model on the topic Me and My Needs in the fourth grade of elementary school. The study employed a Classroom Action Research (CAR) design conducted in two cycles consisting of planning, action, observation, and reflection. The participants were 25 fourth-grade students of SDN 1 Kandangan Kota, comprising 15 female and 10 male students. Data were collected through classroom observation, achievement tests, and questionnaires, and analyzed using descriptive quantitative and qualitative techniques. The findings revealed that the implementation of the Problem Based Learning model improved both the learning process and learning outcomes. Classical learning mastery increased from 60% in Cycle I to 92% in Cycle II. Teacher performance improved to 97.1% (very good category), while student learning activities increased to 97.5% (very active category). In addition, students' responses toward the learning process reached 92% (very good category). Unlike previous PBL studies that generally focused on only one or two aspects (such as learning outcomes or critical thinking skills), this study demonstrated consistent improvement across four indicators simultaneously — teacher performance, student activity, learning outcomes, and student responses — within a single set of actions. These findings indicate that the Problem Based Learning model is effective in improving elementary students' learning activities and learning outcomes in IPAS learning